2020
DOI: 10.1080/09588221.2020.1802601
|View full text |Cite
|
Sign up to set email alerts
|

Quizlet and podcasts: effects on vocabulary acquisition

Abstract: To date, several studies have investigated the potential benefits of using Quizlet and podcasts for vocabulary development. However, they have mainly focused on the use of available material, and its effects on receptive vocabulary acquisition and students' motivation. In contrast, relatively little has been done to study the effects of studentgenerated podcasts and Quizlet flashcards sets on second language vocabulary acquisition including productive skills. Hence, the present study seeks to analyze and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
4
15
0
1
Order By: Relevance
“…Similarly, items "I found Quizlet useful for my autonomous learning" and "Quizlet made the subject more enjoyable, fun, and attractive" scored 4.5 points, very close to the previous two items. These results are in congruence with other studies (e.g., Anjaniputra & Salsabila, 2018;Barr, 2016;Bueno-Alastuey & Nemeth, 2020;Chien, 2015;Dizon, 2016;Nguyen et al, 2022;Platzer, 2020;Setiawan & Wiedarti, 2020) showing that the use of the Quizlet application in Technology Assisted Language Learning has a positive impact in improving students' vocabulary acquisition while also fostering students' autonomy and motivation.…”
Section: Findings and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, items "I found Quizlet useful for my autonomous learning" and "Quizlet made the subject more enjoyable, fun, and attractive" scored 4.5 points, very close to the previous two items. These results are in congruence with other studies (e.g., Anjaniputra & Salsabila, 2018;Barr, 2016;Bueno-Alastuey & Nemeth, 2020;Chien, 2015;Dizon, 2016;Nguyen et al, 2022;Platzer, 2020;Setiawan & Wiedarti, 2020) showing that the use of the Quizlet application in Technology Assisted Language Learning has a positive impact in improving students' vocabulary acquisition while also fostering students' autonomy and motivation.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…The vast majority of studies on Quizlet so far have focused on the effect of Quizlet on vocabulary acquisition (see e.g., Anjaniputra & Salsabila, 2018;Barr, 2016;Bueno-Alastuey & Nemeth, 2020;Chaikovska & Zbaravska, 2020;Chien, 2015;Dizon, 2016;Dreyer, 2014;Nguyen et al, 2022;Platzer, 2020;Sanosi, 2018). Thus, there are studies on the benefits of Quizlet on vocabulary acquisition at tertiary level (e.g., Anjaniputra & Salsabila, 2018;Dizon, 2016;Nguyen et al, 2022;Platzer, 2020) and secondary level (e.g., Cinar & Ari, 2019), on low-proficiency (e.g., Sanosi, 2018) and high-proficiency students (e.g., Bueno-Alastuey & Nemeth, 2020).…”
Section: Quizlet and Vocabulary Acquisitionmentioning
confidence: 99%
“…As expected, our research revealed that mastering vocabulary with Quizlet results in better learning outcomes. These findings are congruent with the results of the previous research on Quizlet as a vocabulary learning tool (Sanosi, 2018;Al-Malki, 2020;Özer & Zeynep , 2017;Bueno-Alastuey & Nemeth, 2020;Ulla, Perales, & Tarrayo, 2020;Kose, Cimen, & Mede, 2016). In these publications, the authors advocate for Quizlet`s potential in creating a favourable learning environment for vocabulary performance enhancement.…”
Section: Discussionsupporting
confidence: 88%
“…For example, students can listen to a pronunciation model, learn the word's definition, spell the words they hear, check their progress, play review games, and take random practice tests. These pre-determined vocabulary-learning activities help expose users to necessary vocabulary with alternative interactions [23]. The activities used in the study were designed by the first author.…”
Section: Methodsmentioning
confidence: 99%